PERANCANGAN SISTEM INFORMASI PEMELIHARAAN ROW (RIGHT OF WAY) PADA JARINGAN DISTRIBUSI DI PT. PLN ULP AMPERA - Muhamad Akbar Pratama; Muhamad Kadafi (Jurnal Riset Teknik Komputer, 2026)
The development of information technology encourages various institutions to carry out digital transformation, including in the electricity sector. PT PLN (Persero) Unit Layanan Pelanggan (ULP) Ampera has the responsibility to maintain the reliability of electricity distribution, one of which is through the maintenance of the Right of Way (ROW). However, the ROW maintenance process is still carried out manually, starting from recording work locations, monitoring field activities, to reporting work results. This condition causes data management to be less effective, time-consuming, and prone to recording errors. This study aims to design a web-based ROW maintenance information system to support monitoring, recording, and reporting processes in a more structured and integrated manner. The system design is carried out by utilizing Figma as a collaborative design tool to produce a user-friendly interface and to involve users in the development process. The software development method used is the waterfall method, which includes the stages of requirements analysis, system design, implementation, and testing. The results of this study are in the form of a ROW maintenance information system design that is able to integrate maintenance data into a centralized platform. This system is expected to improve the effectiveness of data management, accelerate decision-making processes, and support the reliability of electricity distribution networks at PT PLN ULP Ampera. In addition, this research provides practical experience for students in applying information system knowledge to real-world problems in the workplace.